Marketing Analytics Roadmap: Methods, Metrics, and Tools - Rackley, Jerry (Springer, 2015)
Many managers view marketing as a creative endeavor, not something that is measurable or manageable by numbers. But today’s leaders in the C-suite demand greater accountability. They want to know that they are getting a return on their marketing investment. And to get that ROI number, you need analytics. This expectation is intimidating for the many sales and marketing managers who rely on marketing instincts, not metrics, to do their work. But Marketing Analytics Roadmap: Methods, Metrics, and Tools demonstrates that employing analytics isn't just a way to keep the CEO off your back. It improves marketing results and ensures marketers a seat at the table where big decisions get made.